Perception of Smile Aesthetics of Patients with Anterior Malocclusions and Lips Influence: A Comparison of Dental Professionals’, Dental Students,’ and Laypersons’ Opinions - Khaled Khalaf; Zahra Seraj; Hesham Hussein (International Journal of Dentistry)
Objectives. The aim of the study was to evaluate the perception of smile aesthetics in patients with varying degrees of anterior crowding and spacing among dental specialists, dentists, dental students, and laypersons and to assess the effect of the lips position. Materials and Methods. Clinical photos of cases of anterior crowding (mild, moderate, and severe) and spacing (mild, moderate, and severe) with and without the associated lips were used. The images were evaluated by 250 persons including dental specialists, dentists, dental students, and laypersons using the rating scale method, (extremely unaesthetic to extremely aesthetic, 1 to 5, respectively). Nonparametric tests were used to analyse the data on SPSS version 24. Results. According to the 250 responses, the aesthetic perception of all severities of anterior crowding and mild and moderate spacing was found to be more aesthetic when displayed with the lips (p<0.05). Additionally, the higher the level of dental education, the lower the aesthetic perception with and without the lips (p<0.05). Conclusions. The lips play a significant role in improving the aesthetics of crowded anterior teeth and spaced anterior teeth. Dental educational level influences the aesthetic perception of anterior crowding and spacing. This may have an impact on treatment planning and need for orthodontic intervention.